2018
DOI: 10.1007/s00428-018-2384-3
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant 1p36 deletion and TNFRSF14 mutations in primary cutaneous follicle center lymphoma frequently expressing high levels of EZH2 protein

Abstract: Primary cutaneous follicle center lymphoma (PCFCL) is an indolent variant of follicular lymphoma (FL) with limited information available on the genetic background of the disease. The genetic hallmark of nodal FL, the t(14;18) translocation, affecting the BCL2 gene, is rare in PCFCL. Loss of 1p36, the most common secondary chromosomal abnormality in nodal FL, has been recently reported in 16.7% of PCFCL cases. In order to further characterize PCFCL, 21 cases were analyzed using interphase fluorescence in situ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…Prior studies assessing BCL2 gene rearrangements and BCL2 expression in cutaneous FL (.300 cases of PCFCL and 50 of SCFL, combined). 3,4,[6][7][8][9]44,[48][49][50][51] have shown that, although BCL2 gene rearrangements are much more commonly associated with SCFL than PCFCL, a subset of cases of PCFCL (up to 30% of cases) also have this genetic alteration. Almost all cases of SCFL and 20% to 86% of those of PCFCL in prior studies have been shown to have BCL2 expression, including nearly all cases of SCFL and PCFCL that have BCL2 gene rearrangements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies assessing BCL2 gene rearrangements and BCL2 expression in cutaneous FL (.300 cases of PCFCL and 50 of SCFL, combined). 3,4,[6][7][8][9]44,[48][49][50][51] have shown that, although BCL2 gene rearrangements are much more commonly associated with SCFL than PCFCL, a subset of cases of PCFCL (up to 30% of cases) also have this genetic alteration. Almost all cases of SCFL and 20% to 86% of those of PCFCL in prior studies have been shown to have BCL2 expression, including nearly all cases of SCFL and PCFCL that have BCL2 gene rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 2 of the 3 PCFCL samples with 1p36 deletions (PS01, PS02, PR08) also had concomitant damaging TNFRSF14 mutations, which is consistent with a recent report on PCFCL. 44 Other validated cancerpromoting mutations included single gain-of-function mutations in JAK3, KRAS, FOXO1, CARD11, and RHOA and loss-of-function mutations in TET2, SOCS1, and B2M (Figures 2 and 3; supplemental Tables 2-7). Two cases had loss-of-function FAS mutations.…”
Section: Pcfclmentioning
confidence: 99%
See 1 more Smart Citation
“…BCL2‐positive cases with CD10 expression and BCL2 gene translocation makes it advisable to rule out a systemic origin. Only mutations in the TNFRSF14 gene have been reported in PCFCL, usually in combination with 1p36 deletion 10 . All these facts together allowed us to exclude the diagnosis of PCFCL with a diffuse pattern.…”
Section: Figurementioning
confidence: 93%
“…As in nFL, PCFCL also frequently show deletions of 1p36/ TNFRSF14 [24,27]. In PCFCL, loss of 1p36 and BCL2R appear to be mutually exclusive, whereas they are often concurrent in nFL [32]. Mutations of TNFRSF14 are similarly frequent in both entities (30-40%) but the mutational profile of PCFCL differs from that of nFL harbouring BCL2R in having lower frequencies of mutations in chromatin modifiers (CREBBP, KMT2D, EZH2) and BCL2, and a higher incidence of mutations in TNFAIP3 (Table 2) [24].…”
Section: Primary Cutaneous Follicle Centre Lymphomamentioning
confidence: 97%